Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(2.53.12+4.6.87-3.8.40\)
\(=2.53.4.3+4.6.87-3.2.4.40\)
\(=4.6.53+4.6.87-4.6.40\)
\(=4.6.\left(53+87-40\right)\)
\(=4.6.100=2400\)
B=4*13/9*3-4/3*40/9
B=4/3*13/9-4/3*40/9
B=4/3*(13/9-40/9)
B=4/3*(-27)/9
B=4*(-3)/9
B=-4
A=6/7 + 1/7.(2/7+5/7)
A=6/7 + 1/7.7/7=6/7+1/7.1
A=6/7+1/7=7/7=1
\(\frac{5}{6}.\frac{8}{7}+\frac{5}{7}.\frac{2}{3}\)
\(=\frac{5}{7}.\frac{8}{6}+\frac{5}{7}.\frac{2}{3}\)
\(=\frac{5}{7}\left(\frac{8}{6}+\frac{2}{3}\right)\)
\(=\frac{5}{7}\left(\frac{8}{6}+\frac{4}{6}\right)\)
\(=\frac{5}{7}.2=\frac{10}{7}\)
a. x= 2/3 : 3/7
=> x = 14/9
b.x= 11/3 . 8/11
=> x = 8/3
c.x = 2/5 : -1/4
=> x =-8/5
cho mk nhé!
a, = ((100-2):2+1). (100+2):2= 3050
b, =(99-97)+(95-93)+...+ (7-5)+( 3-1)
= 2+2+2+2+...+2+2
có ((99-1):2+1):2= 25
= 2.25
=50
B) 99- 97 + 95 – 93 + 91 – 89 + ... + 7 - 5 + 3 -1
= ( 99 - 97 ) + ( 95 – 93) + (91 – 89) + ... + (7 - 5 ) + (3 - 1)
= 2 + 2+ 2 + ...+ 2 + 2 (có 25 số 2)
= 2.25
= 50
a) 14-(7-x+3)=5-{4-(5- |3| ) }
14-(10-x) = 5-{4-(5-3) }
x +14-10=5-(4-2)
x+4 = 5-2
x+4 =3
x =3-4
x =-1 Vậy x= -1
-7 + [ - (-3) + |6| - (544 + |-6 |) ] = 5 - ( 7 - x + 4)
-7+{ 3+6-(544+6) } =5-(11-x)
-7+(9-600) =x+5-11
-7+-591 =x+(-6)
-598 = x+ (-6)
x =-598 - (-6)
x = -592
Vậy x= -592
tick mình nha
a.5/2
b.1/9
a) =5/2
b)=1/9
kb nhé